2021
DOI: 10.1080/17843286.2021.1996068
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial prescription in severe COVID-19 and CAP: a matched case-control study

Abstract: Background:In severe coronavirus diseases 2019 (COVID-19), a high and potentially excessive use of antimicrobials for suspected bacterial co-infection and intensive care unit (ICU)-acquired infections has been repeatedly reported. Objectives: To compare an ICU cohort of community-acquired pneumonia (CAP) with a cohort of severe COVID-19 pertaining to co-infections, ICU-acquired infections and associated antimicrobial consumption. Methods: We retrospectively compared a cohort of CAP patients with a cohort of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Second, mortality was most likely influenced by unmeasured confounders, such as the strain on the healthcare system, which was more pronounced in the second wave in Belgium with less postponement of regular care which could have led to a compromised COVID capacity and expertise, in comparison with the first wave (Additional file 1 : Figure S1). Furthermore, studies have demonstrated that bacterial surinfections and fungal infections are frequent in patients with critical COVID-19 [ 36 38 ]. We did not compare the occurrence of ICU-acquired infections in the first versus the second wave which could also have contributed to ICU mortality.…”
Section: Discussionmentioning
confidence: 99%